ART THERAPY DENGAN TEKNIK MENGGAMBAR UNTUK MENURUNKAN KECEMASAN TERHADAP PROSEDUR MEDIS PADA ANAK PENDERITA LEUKEMIA - , Sarah, Dra. Nida Ul Hasanat, MSi., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One of the psychological problems faced by children with leukemia is the anxiety of medical procedures. Anxiety of medical procedures observed in the behavior before undergoing a medical procedures. This study aimed to find the influences of art therapy using drawing techniques in reducing the anxiety of medical procedures. Participans in this study were 3 children with leukemia aged 7 â 11 years. Research design was small N experiment with AB and follow up design. The therapy is intended to the participants individually in 5 sessions. Research instruments were a modification of checklist positive behavior from Favara- Scaco and âfeeling compasâ. Quantitative analysis using visual inspection to analyzed the dynamic of anxiety of medical procedures. Qualitative analysis is carried out by analyzing the result of interview sessions both participants and their family and observing participants behaviors before undergoing medical procedure. The research result shows that art therapy using drawing technique reduces anxiety during medical procedure.